Evaluation of Vermi-Derma bioformulations against blister blight disease of Camellia sinensis (L.) O. Kuntze - Parathiraj, Sappanimuthu; Ponmurugan, Ponnusamy; Mounika, Devaraj; Anitha, Arumugam; Mathew, Siby (Current Botany, 2025)
Blister blight disease caused by an obligate fungal pathogen, Exobasidium vexans is very common in almost all the tea growing regions in India. Due to this disease, the green leaf yield potential and tea quality parameters are significantly affected. In order to control this disease, several fungicide schedules are made available to tea planters. But the fungicide schedules lead to accumulation of fungicide residues in made tea which ultimately affect the export quality. Keeping in mind, studies were undertaken to evaluate the various concentrations of Vermi-derma bioformulations amended with various native biocontrol agents like Trichoderma harzianum (fungi), Pseudomonas fluorescens (bacteria) and Streptomyces sannanensis (actinomycete) against blister blight disease. The results revealed that there was a significant reduction in blister blight disease in the trail plots after imposing various treatments of Vermi-derma bioformulations. Among the treatments tested, a significant disease protection of 72.42±2.08% was registered with copper oxychloride + Contaf fungicides treatment. On the other hand, the highest green leaf yield of 5401±2.27 kg ha-1 made tea was registered with T. harzianum amended with Vermi-derma bioformulations (1:20 ratio) treatment. Similarly, biometric analysis, physiological traits and biochemical constituents were also increased in the same treatment. P. fluorescens and S. sannanensis amended with Vermi-derma bioformulations were found to be on par with each other in terms of disease control and green leaf yield. Increasing all these parameters might be due to the recovery of leaves from E. vexans infection by the action of Vermi-derma bioformulations.